Prototype of sliding whiteboard as physics learning media based on thinking processed review - Marthen Billy Jesajas; Ferdy Semuel Rondonuwu; Wahyu Hari Kristiyanto (Journal of Science and Science Education, 2018)
Whiteboard is one of the learning medias used by the teacher in classroom. It has a great role in physics teaching and learning process. As media of learning, a whiteboard also has an important role in students’ thinking process. This paper discussed about the design of sliding whiteboard based on students’ assimilation of thinking in information processing that written on the whiteboard. The result of sliding whiteboard designs served as a prototype. The prototype was made from 10 cm x 18 cm plywood and rope as a slider. This prototype is expected to became an alternative model in addition to fix stage or theater seat model. In addition, the whiteboard sliding model will be accompanied by a module and user manual. Impact of the prototype on student learning was discussed.